How to prevent the division of the free-enterprise world - Hugh Corbet (Intereconomics, 1972)
Two issues will need to be addressed constructively by the enlarged European Community if the multilateral trade negotiations foreshadowed to begin next year are not to founder. They relate, first, to the division of the free-enterprise world into economic spheres of influence and, secondly, to the isolation of commercial markets for temperate-zone farm commodities.
Keywords: 330; Foreign Trade